Adipsin of the Alternative Complement Pathway Is a Potential Predictor for Preeclampsia in Early Pregnancy - Liu, Min; Luo, Xiaolei; Xu, Qin; Yu, Hongbiao; Gao, Linbo; Zhou, Rong; Wang, Tao (Frontiers in Immunology, 2021)
Objective: The concentrations of complement proteins (adipsin, C3a, and C5a) and soluble endoglin (sENG) in the plasma were measured in this study, and their value as early-pregnancy predictors and potential diagnostic marker of preeclampsia was assessed, respectively. Experimental design: Plasma samples were obtained from healthy and preeclampsia pregnant women before delivery for a cross-sectional study. Plasma samples were collected from healthy and preeclampsia pregnant women throughout pregnancy and postpartum for a follow-up study. Enzyme-linked immunosorbent assays were used to detect plasma levels of several complement proteins (adipsin, C3a, and C5a) and sENG. Results: The plasma levels of adipsin, C5a, and sENG were significantly increased before delivery in pregnant women with preeclampsia. During pregnancy, the plasma adipsin, C5a, and sENG levels were increased from the third trimester in healthy pregnant women; plasma adipsin levels remained stable after delivery, while C3a levels increased in the second trimester and remained stable afterward. Furthermore, levels of adipsin, C5a, and sENG were higher in preeclampsia patients at different stages of pregnancy; the C3a level presents a similar change and no difference was found in the third trimester. In the first trimester, receiver-operating curve (ROC) curve analysis showed that adipsin (AUC, 0.83 ± 0.06, P=0.001) and sENG (AUC, 0.74 ± 0.09, P=0.021) presented high value as predictors of early pregnancy. Conclusions: Adipsin is likely a novel plasma biomarker to monitor the increased risk of preeclampsia in early pregnancy. Moreover, the increased plasma levels of adipsin, C5a, and sENG before delivery may be associated with preeclampsia.